Pengaruh Metode Pemupukan dan Berbagai Jenis Mulsa Terhadap Pertumbuhan dan Hasil Tanaman Stevia (Stevia Rebaudiana Bertoni) dengan Irigasi Tetes - Ahlan Anwari; Arthur Frans Cesar Regar (Berkala Ilmiah Pertanian, 2023)
This study wants to find the best fertilizing method and kind of mulch for better growth and yield of stevia. The research was conducted at October-February in PT. Daya Santosa Rekayasa, Karangploso, Malang at an altitude Â±750 MAMSL. The research uses Split Plot Design using RBSL model with two factors and four replications. The first factor which is also used for the main plot is fertilizing method using fertigation (A1) and conventional method (A2). Second factor also uses as the subplot are black white plastic mulch (U1), rice straw mulch (U2), and without mulch (U3). Nondestructive variable was height of the plant and number of leaves. Destructive variable was observed in harvest time such as fresh weight of plant, fresh weight of yield, dry yield, root length, chlorophyll amount, and sucrose rate. The data will be tested using ANOVA and T-Test, if there is a significant difference, then will be processed again using Duncan Multiple Range Test (DMRT). The result showed that there is no significant interaction between the fertilizing methods and types of mulches in stevia. Fertigation and conventional method give no significant difference in growth or yield stevia but fertigation gives better result in every variable. Types of mulches show that black white plastic mulches give the best impact to height of the plant, number of leaves, fresh weight of plant, fresh weight of yield, dry yield, root length, and chlorophyll amount with fresh yield 11,4 gr each plant and also dry yield 2,27 gr.